Excitable dynamics and coral reef formation: A simple model of macro-scale structure development - Miguel Álvarez-Alegría; Pablo Moreno-Spiegelberg; Manuel A. Matías; Damià Gomila (Physical Review Research)
In this work, we demonstrate that key aspects of the dynamical behavior of coral reefs at the macro scale, which evolve over time scales of centuries, can be accurately described using a model that integrates a few fundamental ecological and physical mechanisms. The model displays excitable behavior, generating various dynamical regimes, including traveling pulses and waves, which lead to the formation of spatial structures similar to those observed in real reefs. Notably, this occurs without relying on a classical pattern formation mechanism, such as the Turing scenario. We conduct a thorough analysis of the model's bifurcations in response to two ecologically significant parameters, laying the foundation for using this model to explain coral reef formation.